Impact of Orthodontic Treatment on the Oral Health-related Quality of Life in Children - Genta Agani Sabah; Mehmet Gümüş Kanmaz (Journal of Behçet Uz Children's Hospital)
Oral health-related quality of life has become an essential measure in dental research and clinical practice, capturing the impact of oral health on an individual’s overall well-being across psychosocial domains. In children and adolescents, oral health-related quality of life assessments differ significantly when compared to adults, with a focus on factors like self image, social acceptance, and school environment. The aim of this article is to present a general review of the relationship between malocclusions and oral health-related quality of life, examining how dental problems, especially those impacting aesthetics, can influence a young patient’s social and emotional well-being. It also emphasizes the effectiveness of orthodontic treatment in enhancing oral health-related quality of life particularly in terms of socio-emotional aspects, underscoring patient-centered care. This review advocates for the integration of oral health-related quality of life measures into clinical decisions to better address patients’ functional and emotional needs, by improving their overall quality of life.